Increasing Vocabulary and Listening Comprehension During Adapted Shared Reading: An Intervention for Preschoolers with Autism Spectrum Disorder. - Laçin, Emre (Journal of Autism & Developmental Disorders, 2024)
Purpose: This study examined the improvement in vocabulary and listening skills of children with ASD through adapted shared reading. It also investigated the generalisation effect of this increase to new books and social validity. Methods: A multiple probe across participants design was used to investigate the effect of ASR (adapted shared reading) on the vocabulary and listening comprehension skills of young children with autism spectrum disorder (ASD). The participants were Turkish-speaking children diagnosed with ASD attending a preschool special education institution in Turkey. The researcher analysed the data obtained from the baseline, intervention, generalization and mastery phases using the visual analysis method. Results: Following the intervention, all three participating children gradually improved their vocabulary and listening comprehension skills. The findings suggest that young children with ASD can participate in and benefit from shared reading interventions with support. Conclusion: The adapted shared reading method (ASR) is an effective method for increasing the vocabulary and listening comprehension skills of young children with ASD.